Optimal Path Routing - Abood, Loay; Shkara, Ahmed (Iraqi Journal of Science, 2024)
Analyzing Google map to find optimal path routing is an important and advancedstrategy in geographic information system (GIS), it provides strong decision supportfor the users in service area.Optimal path routing system built to allows the users, businesses, and militaries tofind the optimal path (shortest and fastest path) between any two points (locations)on a road networks (edges) of Google map image.